Endeavour. The complete ninth season [videorecording (DVD)] - Lewis, Russell, 1963- (Endeavour., 2023)
Spring 1972 brings with it a new start for Morse, having taken time out to deal with the drink. His return to CID coincides with a gruesome discovery in a college garden. The investigation leads him and Thursday to a celebrated orchestra and when a second tragedy hits, they uncover a web of secrets at the company's core.